Synthesis and formulation studies of griseofulvin analogues with improved solubility and metabolic stability - Petersen, Asger B.; Konotop, Gleb; Hanafiah, Nur Hafzan Md; Raab, Marc-Steffen; Krämer, Alwin (European journal of medicinal chemistry, 2017)
Griseofulvin (1) is an important antifungal agent that has recently received attention due to its antiproliferative activity in mammalian cancer cells. Comprehensive SAR studies have led to the identification of 2′-benzyloxy griseofulvin 2, a more potent analogue with low micromolar anticancer potency in vitro. Analogue 2 was also shown to retard tumor growth through inhibition of centrosomal clustering in murine xenograft models of colon cancer and multiple myeloma. However, similar to griseofulvin, compound 2 exhibited poor metabolic stability and aqueous solubility. In order to improve the poor pharmacokinetic properties, 11 griseofulvin analogues were synthesized and evaluated for biological activity and physiological stabilities including SGF, plasma, and metabolic stability. Finally, the most promising compounds were investigated in respect to thermodynamic solubility and formulation studies. The 2′-benzylamine analogue 10 proved to be the most promising compound with low μM in vitro anticancer potency, a 200-fold increase in PBS solubility over compound 2, and with improved metabolic stability. Furthermore, this analogue proved compatible with formulations suitable for both oral and intravenous administration. Finally, 2′-benzylamine analogue 10 was confirmed to induce G2/M cell cycle arrest in vitro.